MEDICAL INFORMATICS AND CYBERNETICS IN HEALTH AND MEDICINE: UNIFIED PROGRAM POSTGRADUATE TRAINING OF DOCTORS AND PHARMACISTS (Part 3) - Mintser, O. P.; Voronenko, Yu. V.; Babintseva, L. Yu.; Mokhnachov, S. I. (Medical Informatics and Engineering, 2017)
...